LEVEL OF STUDENT ATTITUDE TO SCHOOL CLEANLINES IN JUNIOR HIGH SCHOOL AND MADRASAH ALIYAH IN JEMBER - Muhammad Rizqi; Wachju Subchan (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
This study aims to determine how much the level of student care for the cleanliness of the school environment. This research is a descriptive variable research in which the type of research carried out is observation and survey research to find out the level of concern of students towards the cleanliness of the school environment. Data collection using Google Form by giving questionnaire questions to students of An-Nur Rambipuji Islamic Middle School class IX and class X MA An-Nur Rambipuji in Rambigundam Village, Rambipuji District, Jember Regency, the data collected so far are 75 respondents with 35 junior respondents and 40 MA respondents. Limited respondents because not all students can have a Handphone to be able to access the Questionnaire. Observation results are divided into two clusters namely SMP and MA Clusters. The SMP and MA clusters have not so significant differences, namely 33% of SMP students and 27% of MA students in terms of concern for the cleanliness of the school environment, the level of concern for the cleanliness of the SMP cluster school environment is lower than the MA cluster which is 33%. Overall, from all clusters the level of concern for the cleanliness of the school environment was in the unfavorable category because 29% of junior and senior high school students had a low level of concern for environmental cleanliness.